Development of a freeware application for the estimation of inert gas load in common half-time compartments - Buzzacott, Peter; Brett, Kaighley; Chimiak, James; Bouak, Fethi; Herrmann, Johannes; Krishna, Aneesh; Baddeley, Adrian (Undersea and Hyperbaric Medical Society, 2021)
Introduction/Background The package SCUBA for the statistics program R estimates inert gas loads in parallel compartments: for example, Bi.ihlmann's ZH-L 16A. Previous limitations for modeling research include processing single dive profiles, and the resultant time-series compartment pressure estimates must be further processed, (e.g., in R, or exported to a file such as MS Excel) to help determine maximum differentials (e.g., between compartment pressures and ambient pressure). Materials and Methods A graphical user interface (GUI) was developed using the R package Shiny. The GUI allows user-selection of popular Haldanian parallel compartments, or a custom set of 1- to 10-minute incremental compartments (for small-animal decompression modeling). Multiple combinations of oxygen, nitrogen and helium are possible, and multiple dive series profiles can be analyzed in batches. Results A set of 892 individual air dives were combined into 202 repetitive dive profiles (mean 4.4 bounce dives per day). These were imported into SCUBA by the GUI, and the output variables exported to an Excel worksheet, one row per dive series (n=52 columns per dive series): dive series identification number, and for each Bi.ihlmann compartment (n=17, including compartment 1 b) maximum positive difference between inert gas partial pressure (PN2) and inspired gas partial pressure, between PN2 and ambient pressure, and the total partial pressure of inert gas upon surfacing. From these derived output variables Bi.ihlmann a and b values were determined and, from these, Baker-Bi.ihlmann gradient factors reached during each dive we estimated (based on Workman M-values). Summary /Conclusion The new GUI has potential applications in decompression research: for example, comparing gradient factors between dive profiles resulting in DCS and diver/environment matched benign profiles, or in modeling which compartments and supersaturation pressures are likely associated with the appearance of bubbles. The software is freely available from peter.buzzacott@curtin.edu.au